2019
DOI: 10.1103/physrevfluids.4.124306
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of a liquid-saturated granular column on a horizontal plane

Abstract: Laboratory experiments on the collapse of a liquid-saturated granular column on a horizontal plane are reported. The trigger and the resulting dynamics of the collapse when occurring, as well as the shape of the final deposit, are characterized and analyzed in light of some dimensionless parameters, namely, the "column" Bond number Bo, the grain diameter to capillary length ratio d/l c , the initial aspect ratio a, the Stokes number St, and the initial volume fraction φ, by varying the properties of the inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
(86 reference statements)
1
19
0
Order By: Relevance
“…Entanglement is not the only mechanism that can lead to stable piles; such stable granular columns have been reported in the case of cohesive particles [54] and fluid-saturated particles [55]. In [54] Abramian et al conducted discrete and continuous two-dimensional simulations of the slumping of a column of cohesive particles and observed stable and collapsed regimes.…”
Section: Analogy With Other Stable Granular Assembliesmentioning
confidence: 99%
See 2 more Smart Citations
“…Entanglement is not the only mechanism that can lead to stable piles; such stable granular columns have been reported in the case of cohesive particles [54] and fluid-saturated particles [55]. In [54] Abramian et al conducted discrete and continuous two-dimensional simulations of the slumping of a column of cohesive particles and observed stable and collapsed regimes.…”
Section: Analogy With Other Stable Granular Assembliesmentioning
confidence: 99%
“…In [54] Abramian et al conducted discrete and continuous two-dimensional simulations of the slumping of a column of cohesive particles and observed stable and collapsed regimes. In [55] Bougouin et al examined the problem of the slumping of a fluid-saturated column of particles. In their study, varying the "column" Bond number, which compares gravity to capillary effects, also leads to stable and collapsed regimes.…”
Section: Analogy With Other Stable Granular Assembliesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this contribution, we are interested in characterising the failing behaviour of cohesive columns of varying cohe-sive properties. While most works on granular columns, including the collapse of cohesive material, concentrate on the run-out behaviour or the deposit shape after the collapse [21][22][23][24][25][26], the present work focuses on the first instant of the failure. The objective is twofold.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Stokes number which indicates the relative importance of the grain inertia and fluid viscosity effects, grain/fluid density ratio, and initial aspect ratio considerably influence the collapse process and deposition profile (Bougouin & Lacaze, 2018). Research on wet and saturated granular column collapse events has demonstrate that the deposition profile is highly dependent on the water content, Bond number (Artoni et al, 2013;Gabrieli et al, 2013), Stokes number and initial solid volume fraction (Bougouin et al, 2019). Iverson et al (1997) noted that the results of field investigations, laboratory experiments and theoretical analysis suggested that the fluidization transformation of landslides can be attributed to the transition of Coulomb failure to partial or complete liquefaction, which is influenced by high pore pressures.…”
mentioning
confidence: 99%